Bile reflux Gastritis Treatment Options and Outcomes - Navid M. Bridget, Shavonne L. Solmaz (Academic Journal of Clinicians, 2024)
Bile reflux also called Alkaline Reflux is one of the causes of Esophageal Reflux , which is more difficult to control medically. When it appears, the symptoms of substernal pain and burning are intense, even preventing the sufferer from leading a normal life. The treatment consists of removing bile from the stomach and cardia to avoid bile or alkaline reflux. This is achieved through an operation, consisting of performing a Roux Y; that is, transforming the Billroth into a biliary diversion. The most common cause of bile or alkaline reflux is stomach surgery: Billroth I Gastrectomy, Billroth II, Vagectomy and Pyloroplasty, operations that were widely performed 20 years ago to treat gastric and/or duodenal ulcers (currently out of use). Although these patients were operated on by open surgery (laparotomy), this complex and difficult intervention, due to the stomach being operated on and the adhesions caused by the laparotomy, can be performed by laparoscopy. It is a complex operation, only achievable by teams with the most experience and the best results.